Single Meaning, Multiple Context and Referents: Pendekatan Intertekstual terhadap Penggunaan Perjanjian Lama dalam Perjanjian Baru - Gilbeth Pramana Saputra (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
The use of the Old Testament (OT) in the New Testament (NT) presents significant hermeneutical challenges, particularly when a single OT text appears to retain a stable meaning while being employed across diverse contexts and referents. This article aims to examine and articulate the concept of single meaning with multiple contexts and referents as an intertextual hermeneutical framework for understanding the relationship between the OT and NT. This study employs a qualitative-descriptive method using a hermeneutical-intertextual approach, including textual analysis, biblical scholarship review, and engagement with contemporary hermeneutical theory. The findings demonstrate that NT authors do not negate the original meaning of OT texts; rather, they interpret and expand these texts within new contexts shaped by christological fulfillment and progressive revelation. Consequently, a single textual meaning may be expressed through multiple contexts and referents without compromising theological coherence. This study concludes that this approach provides a responsible interpretive model that upholds fidelity to the original meaning while accounting for the dynamic nature of biblical revelation.